2019
DOI: 10.3389/fneur.2019.00623
|View full text |Cite|
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of an Exercise Program Requiring Minimal In-person Visits for Youth With Persistent Sport-Related Concussion

Abstract: Objective: To evaluate feasibility and acceptability of a sub-threshold exercise program with minimal in-person visits to treat youth with persistent sport-related concussion, and explore efficacy for improving concussive symptoms, health-related quality of life, and fear-avoidance. Study design: We conducted a pilot randomized controlled trial comparing a 6 week sub-threshold exercise program requiring only two in-person visits to active control (stretching) for 12–18 year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…In other words, youth with PPCS may have developed a fear-avoidance response to physical activity, similar to what has been described in youth with chronic pain (25)(26)(27). Other researchers have confirmed elevated levels of fear-avoidance in individuals with PPCS (28,29), and our pilot study of an in-person delivered exercise program for concussion (the Subthreshold Exercise Program, or STEP) (18), demonstrated that fear-avoidance decreased in parallel with concussive symptoms (18). Interventions that encourage youth to exercise despite fears of exacerbating symptoms have been shown to be an effective approach to improving function in individuals with chronic pain (30).…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…In other words, youth with PPCS may have developed a fear-avoidance response to physical activity, similar to what has been described in youth with chronic pain (25)(26)(27). Other researchers have confirmed elevated levels of fear-avoidance in individuals with PPCS (28,29), and our pilot study of an in-person delivered exercise program for concussion (the Subthreshold Exercise Program, or STEP) (18), demonstrated that fear-avoidance decreased in parallel with concussive symptoms (18). Interventions that encourage youth to exercise despite fears of exacerbating symptoms have been shown to be an effective approach to improving function in individuals with chronic pain (30).…”
Section: Introductionsupporting
confidence: 80%
“…Future research with a randomized controlled trial is needed to ensure improvement in symptoms is not due to the passage of time. The MSTEP intervention effect (i.e., decline in concussive symptoms) was similar to an in-person exercise program (STEP) at 3 weeks, but slightly less strong at 6 weeks (18). We also noted improvements in depression, anxiety, sleep, and health-related quality of life, all of which paralleled declines in concussive symptoms.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations